Prospective Evaluation of Dietary Treatment in Childhood Constipation: High Dietary Fiber and Wheat Bran Intake Are Associated With Constipation Amelioration - Maffei, Helga Verena Leoni [UNESP]; Vicentini, Andrea Pereira [UNESP] (Lippincott Williams & Wilkins, 2011)
Objectives: The aim of the study was to evaluate, over 24 months, the intake of dietary fiber (DF) and the bowel habit (BH) of constipated children advised a DF-rich diet containing wheat bran.Patients and Methods: BH and dietary data of 28 children with functional constipation defined by the Boston criteria were obtained at visit 1 (V1, n = 28) and at 4 follow-up visits (V2-V5, n = 80). At each visit the BH was rated BAD (worse/unaltered; improved but still complications) or RECOVERY (REC) (improved, no complications; asymptomatic), and a food intake questionnaire was applied. DF intake was calculated according to age (year)+5 to 10 g/day and bran intake according to international tables. Nonparametric statistics were used.Results: Median age (range) was 7.25 years (0.25-15.6 years); 21 children underwent bowel washout (most before V1/V2), and 14 had the last visit at V3/V4. DF intake, bran intake, and the BH rate significantly increased at V2 and remained higher than at V1 through V2 to V5. At V1, median DF intake was 29.9% below the minimum recommended and at the last visit 49.9% above it. Twenty-four children accepted bran at 60 visits, at which median bran intake was 20 g/day and median proportion of DF due to bran 26.9%. Children had significantly higher DF and higher bran intake at V2 to V5 at which they had REC than at those at which they presented BAD BH. DF intake > age+10 g/day was associated with bran acceptance and REC. At the last visit 21 children presented REC (75%); 20 of them were asymptomatic and 18 were off washout/laxatives.Conclusions: High DF and bran intake are feasible in constipated children and contribute to amelioration of constipation.
Keywords: bowel habit; children; constipation; dietary fiber; wheat bran